A new tool for modelling the decompression behaviour of CO2 with impurities using the Peng-Robinson equation of state. (15th November 2017) - Dall'Acqua, D.; Terenzi, A.; Leporini, M.; D'Alessandro, V.; Giacchetta, G.; Marchetti, B.
Highlights: A new code for the calculation of the expansion wave curves for CO2 -rich mixture. Sound velocity in two-phase region is calculated using Nichita's method. The characteristic plateau of the expansion wave curve is well predicted. The PR EoS produces results with an accuracy comparable to the GERG2008 EoS. Abstract: Carbon capture and storage is considered as promising technique by the scientific community to reduce CO2 emissions and is composed by three different stages: CO2 capture, transportation and storage. The capturing plant has to be installed where processes involving large CO2 emissions, as power generation from fossil fuel, concrete and iron plants are present. The captured CO2 in real applications will be likely a CO2 dominated mixture with a content of several impurities, depending on the capture process which presence affects the thermo-physical properties of the pure CO2, especially increasing the vapour pressure curve. Such behaviour plays an important role in the control of the ductile fracture, whenever the CO2 is transported using pipelines. In the unfortunate event of a pipeline failure, the study of the pipeline decompression can be useful to estimate whether the fracture will remain confined or will propagate. The residual pressure acting on the crack tip of the pipeline represents the energy source governing the fracture's propagation. The pressure profile is given by the expansion wave, which propagates along the pipeline during the fracture. In the literature, it is common practice to model the expansion wave by assuming one-dimensional isentropic decompression. In this study, a new code developed by the authors for modelling the decompression behaviour in the fluid is presented. The code is based on the Peng-Robinson equation of state with the Peneloux correction correlation matching the density of pure components to experimental data. The sound velocity in the two-phase region has been modelled with the method proposed by Nichita et al., which increase the accuracy of prediction with respect to the most popular Wood's method. The code was validated against experimental and numerical data relating to hydrocarbon gas mixtures and CO2 -rich mixtures. In particular, the results obtained for the hydrocarbon gas mixture decompression have been compared with experimental data and the predictions calculated by the software GASDECOM, in order to assess the accuracy of the code, that was then utilized to calculate the expansion wave curves for CO2 -rich mixtures. The results obtained have been compared with experimental data and with predictions generated by the GERG2008 equation of state, found in literature. The simulated expansion wave curves show a good agreement with the experimental data for the tested compositions, especially for the plateau characterising the two-phase transition of rich gas compositions. The plateau corresponds to the saturation pressure, which is a key parameter for the fracture propagation control in CO2 pipelines, since the material toughness required to prevent a propagating ductile fracture is determined by applying the condition that the fracture propagation curve does not cross this value.